Incidence and Malignancy Rate of Bethesda Category III Thyroid Lesions in A Tertiary Hospital - Celes, Aneeshya; Fernandes, Hilda (Annals of Pathology and Laboratory Medicine, 2020)
Background: The introduction of The Bethesda System for Reporting Thyroid Cytopathology in 2010 provided the opportunity to establish worldwide standard reporting and terminology guidelines diagnostic category in reporting of thyroid FNAC. Indeterminate lesion included in the category III are those with insufficient degree of atypia to qualify for any of the suspicious categories. This study was conducted to determine the incidence and malignancy rate of Bethesda category III thyroid lesions. Methods: A two- and half-year retrospective study was conducted in Father muller medical college. Thyroid lesion which were diagnosed as Bethesda category III on fine needle aspiration cytology during the study period were included. The cytology-histopathological correlation was done where ever available to calculate the incidence and malignancy rate of this category. Result: A total of 1397 cases underwent thyroid FNA during the study period. Out of this, 57 cases were reported as Bethesda category III lesion. The incidence rate of Bethesda category III lesions in the study was 4.08%. Twenty-one cases had histopathology correlation. The malignancy rate was found to be 38.09%. Conclusion: The Bethesda category III still remains a very challenging group with a large and varied range of diagnosis. The risk of malignancy might be higher that what is currently estimated for this category. Sub-classification of this category might help in predicting the nature of lesion better and aid patient management more accurately.